The ZZ domain as a new epigenetic reader and a degradation signal sensor - Zhang, Yi (Crit Rev Biochem Mol Biol, 2019)
Although relatively small in size, the ZZ-type zinc finger (ZZ) domain is a versatile signaling module that is implicated in a diverse set of cell signaling events. Here, we highlight the most recent studies focused on the ZZ domain function as a histone reader and a sensor of protein degradation signals. We review and compare the molecular and structural mechanisms underlying targeting the amino-terminal sequences of histone H3 and arginylated substrates by the ZZ domain. We also discuss the ZZ domain sensitivity to histone PTMs and summarize biological outcomes associated with the recognition of histone and non-histone ligands by the ZZ domain-containing proteins and complexes.